Relationship between emotional labor, work stress, employee creativity, and turnover intention: study on Indonesian bank frontliners - Devi Intan Satyaningrum; Indi Djastuti (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2020)
This study examines the effects of emotional labor on work stress, employee creativity and turnover intention, and examines the role of work stress as a mediator. The study was conducted in a limited way to the 90 employees of the Semarang branch of the BTN bank frontliners. The analysis using SEM PLS suggested that emotional labor had a positive effect on work stress and turnover intention but was not significant on employee creativity. Furthermore, work stress has a negative effect on employee creativity and a positive effect on turnover intention, and in this study proves that work stress mediated the influence of emotional labor on employee creativity and on turnover intention.